The Influence of Internships on the Development of Soft Skills of Office Administration Education Students - Sirajuddin Saleh; Lala Lala; Muh. Darwis (Pinisi Journal of Education and Management, 2023)
This research was conducted to determine the effect of internships on the development of soft skills of Office Administration Education Students, Faculty of Social Sciences and Law, Makassar State University. The population in this study was 95 people and the sample was 95 people. While the data analysis techniques used are descriptive statistics using percentages and for inferential statistical analysis techniques using data normality tests, moment product correlation analysis, simple line ar regression analysis andpartial t tests.  From the test results show that the indicators of the internship variable are in the very good category while the learning motivation variable is in the very high category. Based on the results of the product moment correlation analysis, there is a relationship between the two variables. So it can be concluded that there is a significant influence between internships on the development of soft skilss Office Administration Education Students of the Faculty of Social Sciences and Law, Makassar State University